2014
DOI: 10.1017/s109285291400011x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary gland volume in at-risk mental state for psychosis: a longitudinal MRI analysis

Abstract: This, together with the result of our previous study, could indicate that the perceived level of stress in ARMS patients is constantly high from very early onward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
1
10
1
Order By: Relevance
“…Another potential reason is that psychotic disorders are complex with regard to clinical symptoms, as well as pathogenesis and pathophysiology, which is why enhanced pituitary volume in UHR and FES patients could be related to a subgroup of patients. Some studies have reported differences between converters and non-converters in an UHR sample (Buschlen et al, 2010;Garner et al, 2005) whereas other studies were unable to replicate these findings (Gruner et al, 2012;Walter et al, 2015) . Finally, measuring the pituitary volume provides information about changes in the corticotroph cells, which is important since the anterior pituitary gland also contains a variety of other cell types.…”
Section: Pituitary Glandmentioning
confidence: 98%
“…Another potential reason is that psychotic disorders are complex with regard to clinical symptoms, as well as pathogenesis and pathophysiology, which is why enhanced pituitary volume in UHR and FES patients could be related to a subgroup of patients. Some studies have reported differences between converters and non-converters in an UHR sample (Buschlen et al, 2010;Garner et al, 2005) whereas other studies were unable to replicate these findings (Gruner et al, 2012;Walter et al, 2015) . Finally, measuring the pituitary volume provides information about changes in the corticotroph cells, which is important since the anterior pituitary gland also contains a variety of other cell types.…”
Section: Pituitary Glandmentioning
confidence: 98%
“…However, it is important to note that, with the exception of one study of GHR youth, in which a positive association between pituitary volume and schizotypal symptoms was observed (Shah et al, 2015b), previous studies of at-risk individuals have failed to observe a correlation between increased pituitary volume and more severe symptoms, including positive and negative psychotic symptoms, anxiety, and depression (Garner et al, 2005, Mondelli et al, 2008, Takahashi et al, 2009a, Takahashi et al, 2013, Walter et al, 2014.…”
mentioning
confidence: 92%
“…While CHR youth in all four samples were antipsychotic-naïve or minimally-treated, negative symptoms were notably higher among CHR participants in the study by Takahashi at colleagues, possibly reflecting more advanced illness. Moreover, while two of these studies reported that CHR youth who transitioned to psychosis within 1-3 years were characterized by larger pituitary volumes at study commencement compared to CHR individuals who did not (Garner et al, 2005, Büschlen et al, 2011, these findings were not replicated in the two subsequent investigations (Takahashi et al, 2013, Walter et al, 2014, possibly reflecting limited statistical power related to the small number of participants in the transitioned groups. Finally, no pituitary volume abnormalities were observed in a sample of children (11-14 years) at elevated risk for schizophrenia due to the presence of developmental antecedents of the disorder (Cullen et al, 2015b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our pituitary findings are generally in line with previous MRI studies in clinical high-risk subjects; the individuals who later develop psychosis may exhibit pituitary expansion prior to psychosis onset ( 10 , 40 ), but those without psychosis onset also have similar pituitary changes ( 10 , 11 ). Although some high-risk studies did not replicate these findings ( 7 , 47 ), probably due to small sample sizes and/or differences in various influencing factors as described below, pituitary expansion reported in psychosis is thought to reflect HPA hyperactivity and a subsequent increase in the size and number of corticotrophs, whereas chronic HPA activation could cause pituitary atrophy by reducing the function of the cells producing other pituitary hormones ( 15 , 48 ). Thus, the pituitary volume in the course of psychosis likely reflects state-related HPA axis dysregulation, which is associated with illness stages and symptom severity ( 15 ), antipsychotic medication ( 2 , 49 ), demographic characteristics [e.g., age, gender ( 50 , 51 )], and other mediating factors.…”
Section: Discussionmentioning
confidence: 99%